Pemberdayaan Kelompok Penggerak Pariwisata (Kompepar) Pasir Batang melalui Pembuatan Pembibitan Tanaman Rehabilitasi - Supartono, Toto; Nugraha, Dadan; Wiharno, Herma; Hidayatulloh, Syahrul; Mafaz, Mihra Fauzia; Anggraeni, Dina Mariana; Menara, Sekar Amalia (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
The partner or target group for this community service activity is Kompepar Pasir Batang which is located in Karangsari Village, Darma District, Kuningan Regency. The activity area of Kompepar is the Pasir Batang Block which is part of the Gunung Ciremai National Park area. One of the problems faced by these partners is the difficulty of obtaining plant for rehabilitation activities around the partner's activity locations. Therefore, the aim of this service activity is to help provide a nursery for types of rehabilitation plants. The implementation methods used are counseling, training and empowerment. This activity can run smoothly as expected. This activity also received appreciation from the local village government and received full support from partners. Partners are actively involved in every stage of the activity. For the sustainability of the program, assistance by the Community Service Team will also continue so that the positive impact of the activities can be felt in real terms by many parties.